Endougenous Timing in a Mixed Duopoly - Rabah Amir; Giuseppe De Feo (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
This paper applies the framework of endogenous timing in games to mixed quantity duopoly, wherein a private domestic or foreign firm competes with a public, welfare maximizing firm. We show that simultaneous play never emerges as a subgame-perfect equilibrium of the extended game, in sharp contrast to private duopoly games. We provide sufficient conditions for the emergence of public and/or private leadership equilibrium. In all cases, private profits and social welfare are higher than under the corresponding Cournot equilibrium. From a methodological viewpoint we make extensive use of the basic results from the theory of supermodular games in order to avoid common extraneous assumptions such as concavity, existence and uniqueness of the different equilibria, whenever possible. Some policy implications are drawn, in particular those relating to the merits of privatization.
Keywords: C72; D43; H42; L13; 330; Mixed markets; endogenous timing; Cournot equilibrium; Stackelberg equilibrium; privatization